Organic components of airborne dust influence the magnitude and kinetics of dendritic cell activation. (August 2018) - Boucher, Magali; Blais Lecours, Pascale; Létourneau, Valérie; Veillette, Marc; Duchaine, Caroline; Marsolais, David
Abstract: Bioaerosol exposure in highly contaminated occupational settings is associated with an increased risk of disease. Yet, few determinants allow for accurate prediction of the immunopathogenic potential of complex bioaerosols. Since dendritic cells are instrumental to the initiation of immunopathological reactions, we studied how dendritic cell activation was modified in response to individual agents, combined microbial agents, or air sample eluates from highly contaminated environmental settings. We found that combinations of agents accelerated and enhanced the activation of in vitro -generated murine bone marrow-derived dendritic cell cultures, when compared to individual agents. We also determined that endotoxins are not sufficient to predict the potential of air samples to induce bone marrow-derived dendritic cell activation, especially when endotoxin levels are low. Importantly, bone marrow-derived dendritic cell activation stratified samples from three environmental settings (swine barns, dairy barns, and wastewater treatment plants) according to their air quality status. As a whole, these results support the notion that the interplay between bioaerosol components impacts on their ability to activate dendritic cells and that bone marrow-derived dendritic cell cultures are promising tools to study the immunomodulatory impact of air samples and their components. Highlights: Predicting the immunopathogenic impact of complex bioaerosols remains a challenge. Endotoxin levels are not sufficient to predict dendritic cell activation in vitro. Combination of bioaerosol components modifies dendritic cell maturation in vitro. Dendritic cell activation by air samples stratifies occupational settings by class.